2003
DOI: 10.1007/s00125-003-1239-9
|View full text |Cite
|
Sign up to set email alerts
|

The diabetes prone BB rat model of IDDM shows duration of breastfeeding to influence Type 1 diabetes development later in life

Abstract: Besides genetic background, environmental factors such as food ingredients and viral infections have been indicated as important and possibly decisive elements for the induction of insulin-dependent diabetes mellitus (IDDM). Our data show that diabetes development in diabetes-prone (DP)-BB rats can be delayed and prevented by prolonging the nursing period of these rats. These results provide experimental evidence strengthening human epidemiological data that the duration of exclusive breastfeeding influences d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Autoimmune diabetes incidence of the different treatment groups Figure 1 shows that prolonged exclusive breastfeeding (until 31 days) partially protected against autoimmune diabetes development, confirming our previous report [8]. Rats that received exclusive prolonged breastfeeding followed by a conventional rodent diet displayed an autoimmune diabetes incidence of 46%, compared to 84-89% in the other groups (p < 0.05, log rank test).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Autoimmune diabetes incidence of the different treatment groups Figure 1 shows that prolonged exclusive breastfeeding (until 31 days) partially protected against autoimmune diabetes development, confirming our previous report [8]. Rats that received exclusive prolonged breastfeeding followed by a conventional rodent diet displayed an autoimmune diabetes incidence of 46%, compared to 84-89% in the other groups (p < 0.05, log rank test).…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, human studies are limited in their analysis of the actual effects of diet supplementation and breastfeeding on the (mucosal) immune system. Previously, we have shown that prolonging the exclusive (only breast milk) suckling period in bio-breeding diabetes-prone (BBDP) rats, a rat model that develops autoimmune diabetes spontaneously, decreases the autoimmune diabetes incidence from 80 to 40% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these animal models of T1D also showed that the moment of exposure to wheat proteins is important for the development of T1D. Delaying the exposure to diabetogenic wheat proteins by prolonging the breastfeeding period reduced T1D development in the BBDP rats 41 . Furthermore, exposing neonatal rats or mice to diabetogenic wheat components or bacterial antigens reduced T1D incidence, which is probably due to the induction of immunological tolerance 36,39,42 …”
Section: Gliadin As An Environmental Component Of Autoimmunitymentioning
confidence: 98%
“…Delaying the exposure to diabetogenic wheat proteins by prolonging the breastfeeding period reduced T1D development in the BBDP rats. 41 Furthermore, exposing neonatal rats or mice to diabetogenic wheat components or bacterial antigens reduced T1D incidence, which is probably due to the induction of immunological tolerance. 36,39,42 Rats that were fed wheat protein-based diets develop T1D and display a mild celiaclike enteropathy.…”
Section: Type 1 Diabetesmentioning
confidence: 99%